A Kingdom of Stargazers : Astrology and Authority in the Late Medieval Crown of Aragon - Ryan, Michael A. (Book collections on Project MUSE., 2011)
Astrology in the Middle Ages was considered a branch of the magical arts, one informed by Jewish and Muslim scientific knowledge in Muslim Spain. As such it was deeply troubling to some Church authorities. Using the stars and planets to divine the future ran counter to the orthodox Christian notion that human beings have free will, and some clerical authorities argued that it almost certainly entailed the summoning of spiritual forces considered diabolical. We know that occult beliefs and practices became widespread in the later Middle Ages, but there is much about the phenomenon that we do not understand. For instance, how deeply did occult beliefs penetrate courtly culture and what exactly did those in positions of power hope to gain by interacting with the occult? In A Kingdom of Stargazers, Michael A. Ryan examines the interest in astrology in the Iberian kingdom of Aragon, where ideas about magic and the occult were deeply intertwined with notions of power, authority, and providence. -- Book jacket.